MELOTHRIA (CUCURBITACEAE): A NEW GENUS RECORD OF NATURALIZED CUCUMBER IN SUMATRA - Wendy Achmmad Mustaqim; Hirmas Fuady Putra (PTTI, 2020)
Melothria (Cucurbitaceae): A New Genus Record of Naturalized Cucumber in Sumatra. Floribunda 6(5): 183–187. — The first record of a naturalized cucumber genus Melothria (Cucurbitaceae) is presented for Sumatra, represented by one cosmopolitan species Melothria pendula. The species has been found during an exploration in the northern part of the island. A morphological description, distribution map, brief discussions, and photographs are given.